2011
DOI: 10.1007/s00784-011-0583-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of smoking behaviour in the dental setting. A study comparing self-reported questionnaire data and exhaled carbon monoxide levels

Abstract: The present study validated the accuracy of data from a self-reported questionnaire on smoking behaviour with the use of exhaled carbon monoxide (CO) level measurements in two groups of patients. Group 1 included patients referred to an oral medicine unit, whereas group 2 was recruited from the daily outpatient service. All patients filled in a standardized questionnaire regarding their current and former smoking habits. Additionally, exhaled CO levels were measured using a monitor. A total of 121 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…The results of the present study show a strong association between self-reported smoking habits and the measurement of exhaled CO levels (Tables 3 and 4). The present study corroborates data from a previous study [12], assessing exhaled CO levels of patients from an oral medicine unit and daily outpatient service upon initial presentation. Nevertheless, exhaled CO levels were not yet analysed over a defined period of time in a dental setting, thus also exhibiting the dynamic changes of measured CO levels within the same patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study show a strong association between self-reported smoking habits and the measurement of exhaled CO levels (Tables 3 and 4). The present study corroborates data from a previous study [12], assessing exhaled CO levels of patients from an oral medicine unit and daily outpatient service upon initial presentation. Nevertheless, exhaled CO levels were not yet analysed over a defined period of time in a dental setting, thus also exhibiting the dynamic changes of measured CO levels within the same patients.…”
Section: Discussionsupporting
confidence: 90%
“…The secondary outcome parameters included dynamic changes in questionnaire data analysis such as number of cigarettes consumed per day or the mean packyear value. A previous paper compares the initial data of this group to results of a group of patients recruited from daily outpatient service [12]. All patients examined in the oral medicine unit for the first study were scheduled for a followup visit to reassess their smoking habits 1 year later.…”
Section: Study Sample and Clinical Examinationmentioning
confidence: 99%
“…Limitations of this study include its convenience sampling from one clinic. Smoking rates may have been under reported, although the validity of self‐reported smoking in a sample of clinic patients in a dental school was confirmed when compared with exhaled carbon monoxide levels .…”
Section: Discussionmentioning
confidence: 98%
“…The ‘intention-to-treat’ analysis assumed that all participants lost to follow-up continued to smoke, so our results are more likely to under-report versus over-report program impact. We only used self-reported abstinence; however others have shown that self-report can produce results similar to CO monitoring 27,28 . We were unable to re-assess smoking cessation preoperatively because time to surgery was shorter than anticipated, but any tobacco reduction or cessation likely carries health benefits, even when not directly related to reducing postoperative complications 29,30 .…”
Section: Discussionmentioning
confidence: 99%